In-Vessel Poultry Litter Composting to Facilitate Pathogen Reduction and Biofertilizer Production - F, Felix; F.M, Hashem; P.D., Millner; J., McNelly (International Journal of Biological Research, 2020)
Poultry litter-based organic fertilizers are usually incorporated into soil to improve its structure and fertility to increase crop production, however, poultry litter may also contain a variety of microorganisms which can compromise the safety of fresh produce when applied on agriculture lands. Composting can be a strategy to inactivate these microorganisms while creating a soil amendment beneficial for application to arable agricultural land. The objective of this study was to design and test the effect of moisture and temperature in a mechanically aerated in-vessel composting system for the purpose of reducing bacteria concentration in poultry litter while producing bio fertilizer. The actual composting occurred in four digesters which measured 1.2m x 1.2m x 1.2m. Four treatments were utilized with four different levels of moisture content in each vessel (treatment 1=65%, treatment 2=55% treatment 3=60% treatment 4=50%).Moisture gradually decreased and reached 55%, 44% and 48%, and 38.9% for treatment 1,2,3 and 4, respectively in the final compost product. The maximum average temperatures recorded for test 1, 2, 3 and, 4 were 50.54°C, 50.9 °C, 60.7 and 71.5°C respectively compared to outside temperature (15.4°C), and these temperatures were able to significantly reduce the concentration of total aerobic bacteria, fecal coliform and enterococcus listeria. The initial concentration of the compost piles was approximately 6.57, 6.04 and 3.72 log10 CFU/g of total aerobic bacteria, fecal coliform and enterococcus respectively. After analyzes, all target microorganisms were significantly eliminated. The significant levels of total aerobic bacteria, fecal coliform and enterococcus were p=0.0303, P=0.0258, p=0.0233 respectively. The presence of Salmonella spp. and Listeria spp. were not detected in all sampling period. Results of in-vessel compost analyses revealed a 16.9% N reduction; 10.1% P increase and 33.7% K increase. Moisture content decreased by 52.2% and elevated C/N ratio and pH by 27.7 % and 3.30% respectively. The leachates generated from the in-vessel composting for the first 21 days were analyzed, and the average results for week 1, 2, and 3, were observed to be 1043.7 mg/L, 1335.23mg/L, and 1029.9mg/L.